In Vitro Studies with Recombinant Plasmodium falciparum Apical Membrane Antigen 1 (AMA1): Production and Activity of an AMA1 Vaccine and Generation of a Multiallelic Response - Kennedy, Michael C. (American Society for Microbiology, 2002)
Apical membrane antigen 1 (AMA1) is regarded as a leading malaria blood-stage vaccine candidate. While the overall structure of AMA1 is conserved in Plasmodium spp., numerous AMA1 allelic variants of P. falciparum have been described. The effect of AMA1 allelic diversity on the ability of a recombinant AMA1 vaccine to protect against human infection by different P. falciparum strains is unknown. We characterize two allelic forms of AMA1 that were both produced in Pichia pastoris at a sufficient economy of scale to be usable for clinical vaccine studies. Both proteins were used to immunize rabbits, singly and in combination, in order to evaluate their immunogenicity and the ability of elicited antibodies to block the growth of different P. falciparum clones. Both antigens, when used alone, elicited high homologous anti-AMA1 titers, with reduced strain cross-reactivity. Similarly, sera from rabbits immunized with a single antigen were capable of blocking the growth of homologous parasite strains at levels theoretically sufficient to clear parasite infections. However, heterologous inhibition was significantly reduced, providing experimental evidence that AMA1 allelic diversity is a result of immune pressure. Encouragingly, rabbits immunized with a combination of both antigens exhibited titers and levels of parasite inhibition as good as those of the single-antigen-immunized rabbits for each of the homologous parasite lines, and consequently exhibited a broadening of allelic diversity coverage.